Growth and Selective Etching of Twinned Graphene on Liquid Copper Surface (Small 40/2021). Issue 40 (6th October 2021) - Liu, Fengning; Dong, Jichen; Kim, Na Yeon; Lee, Zonghoon; Ding, Feng
Abstract : Twinned 2D Materials In article number 2103484, Zonghoon Lee, Feng Ding, and co‐workers have predicted the growth of twin boundaries in 2D materials and realized the formation of ultralong and straight twin boundaries in graphene.